GETTING TO KNOW THE BASICS OF ISLAMIC TEACHINGS: A COMPLETE GUIDE TO PAI GRADE 9 - Ali Muzzammil; Arifal Haqqi; M.Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
The results of the study showed that most students understood the main points of the teachings of the faith well, although there were some students who still had difficulty in understanding more abstract concepts, such as destiny and faith in angels. The dominant lecture method used in learning tends to be less effective in facilitating student understanding. However, more interactive approaches such as group discussions have proven to be more effective in improving their understanding. In addition, students' understanding is also influenced by the diversity of social and religious backgrounds. More applicative learning, such as case studies or project-based learning, is recommended to improve students' understanding and connect the faith material with daily life. This research provides important insights on ways to increase the effectiveness of PAI learning at MTS Miftahul Jannah and enrich students' understanding of the Islamic faith.